Star Wars storyboards the original trilogy - Rinzler, J. W.; Lucasfilm, Ltd. (New York Abrams, 2014)
"For the first time, Lucasfilm has opened its archives to present the complete storyboards for the original Star Wars trilogy--the world-changing A New Hope and its operatic sequels, The Empire Strikes Back and Return of the Jedi--as well as never-before-published art from early conceptual and deleted scenes"--Book jacket.
Lucasfilm has opened its archives to present the best of the conceptual storyboards for the three original Star wars episodes, now called IV, V, and VI. Readers will find insight into how these conceptual storyboards helped to contribute both to the creation of the series, and the expansion of the Star Wars universe.
Star Wars : Episode IV : A new hope -- Star Wars : Episode V : The empire strikes back -- Star Wars : Episode VI: Return of the jedi.
Includes index.
Keywords: Empire strikes back (Motion picture).; Return of the Jedi (Motion picture).; Star Wars films -- Miscellanea; aStoryboards; Star Wars films; Storyboards; Miscellanea